The treatment gap in patients with chronic systolic heart failure: a systematic review of evidence-based prescribing in practice - Chin, K.; Skiba, M.; Tonkin, A.; Reid, Christopher; Liew, D.; Krum, H.; Hopper, I. (Springer New York LLC, 2016)
The extent and impact of under-prescribing of evidence-based pharmacological therapies among heart failure patients with reduced ejection fraction (HFREF) in contemporary practice is unclear. We sought to examine the prescribing patterns of angiotensin-converting enzyme (ACE) inhibitors, angiotensin receptor blockers (ARBs), ß-blockers (BBs) and mineralocorticoid receptor antagonists (MRAs), and to quantify the estimated ‘treatment gap’ among HFREF patients in the ‘real-world’ setting. The MEDLINE, PubMed, EMBASE, CINAHL and CENTRAL databases were searched for registry- or survey-based studies which examined the prescribing rates of ACE inhibitors, ARBs, BBs and MRAs among HFREF patients. Searches were limited to those published in the years 2000–2015. A total of 23 reports, including 83,605 patients, were evaluated. Overall, ACE inhibitors/ARBs, BBs and MRAs were prescribed to 79.8, 81.4 and 36.4 % of patients, respectively. The estimated treatment gaps in the overall population were 13.1 % for ACE inhibitors/ARBs, 3.9 % for BBs and 16.8 % for MRAs. The proportion of patients who received =50 % of the guideline-recommended target doses was 72 % for ACE inhibitors, 51 % for ARBs, 49 % for BBs, 53 % for the combination of ACE inhibitors/ARBs and BBs and 83 % for MRAs. Prescribing these drugs according to contemporary guidelines was associated with lower mortality risk. Patients who were elderly, female and with comorbidities were less likely to receive optimal treatment as recommended by the guidelines. ACE inhibitors, ARBs, BBs and MRAs are under-prescribed in eligible HFREF patients. Efforts should be made to improve approaches to closing the treatment gap at both systems of care and individual levels.